1996
DOI: 10.1097/00006534-199605000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Strength of Silicone Breast Implants

Abstract: Rupture and leakage are recognized problems associated with silicone breast implants. Data are scarce about the durability of the silicone shell, and the life span of this device is unknown. The purpose of this study was to investigate the strength of silicone breast implants. Thirty implant shells were subjected to mechanical testing. Twenty-nine of the shells were tested after explanation, and one unused implant served as a control to validate the testing method. Implantation time varied from 4 months to 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 3 publications
1
24
0
Order By: Relevance
“…A correlation between prosthesis aging, rupture, and infiltration of human body components into the prosthesis’ shell and silicone gel has been described in the past [3,4,5,6,7]. Some studies on long-term implantation confirmed lipids absorption with consequent polymer swelling and consequential prosthesis rupture [8,9,10,11]. The Scientific Committee on Emerging and Newly Identified Health Risks (SCENIHR) has recently published an upgrade to its guidelines on the safety of PIP silicone breast implants [12].…”
Section: Introductionmentioning
confidence: 99%
“…A correlation between prosthesis aging, rupture, and infiltration of human body components into the prosthesis’ shell and silicone gel has been described in the past [3,4,5,6,7]. Some studies on long-term implantation confirmed lipids absorption with consequent polymer swelling and consequential prosthesis rupture [8,9,10,11]. The Scientific Committee on Emerging and Newly Identified Health Risks (SCENIHR) has recently published an upgrade to its guidelines on the safety of PIP silicone breast implants [12].…”
Section: Introductionmentioning
confidence: 99%
“…9,15 Fold-flaw cracking of the shell may be due to loss of strength of the silicone shell in a time-dependent manner. 16,17 Leakage caused by fold-flaw fracture is decreased in silicon gel-filled prostheses due to silicon's low coefficient of friction.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have strongly implicated implant age as the prime factor in rupture [24][25][26]. Disruption is directly related to time since implantation.…”
Section: Discussionmentioning
confidence: 99%